Podstawowe zasady wdrażania prośrodowiskowych reform podatkowych w krajach Unii Europejskiej - Borys, Grażyna (Basic Principles for Implementing Pro-Environmental Tax Reforms in the European Union Member Countries, 2005)
The subject matter of the article is the characteristics of three basic principles of pro-environmental tax reforms. These principles are as follows: the principle of clear and detailed definition of the reform's objective, the principle of the reform direction based on the assumption of sustainable development and the principle of adjusting the reform directions to national and international legislative standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 89-95